THE EFFECTIVENESS OF THE USE OF GAMING TECHNOLOGIES IN THE DEVELOPMENT OF DEXTERITY AND COORDINATION AMONG GIRLS AGED 11-13 IN A SCHOOL SETTING (Eureka Journal of Language, Culture & Social Change, 2026)
This article examines the role of physical education in developing agility and coordination in middle school girls, developing goal-directed interaction, and developing sustainable healthy lifestyle habits through the use of game technologies. The study examines the effectiveness of specific physical activities in developing long-term health behaviors and the psychological and social benefits of regular physical activity. The study highlights the importance of incorporating physical education programs into school curricula that are designed to promote not only physical health but also mental well-being in girls, and that tailored physical education activities can significantly contribute to the formation of positive health habits that continue into adulthood.
Keywords: The concept of agility and coordination skills, game technologies, tasks, pedagogical experience, psychological and pedagogical effectiveness, scientific and pedagogical research, high school age, girls.